2013
DOI: 10.3171/2013.1.peds12286
|View full text |Cite
|
Sign up to set email alerts
|

Onyx embolization of intracranial arteriovenous malformations in pediatric patients

Abstract: Object The authors undertook this study to assess the safety and efficacy of Onyx embolization in the treatment of intracranial arteriovenous malformations (AVMs) in pediatric patients. Methods All pediatric Onyx embolization of intracranial AVM cases performed consecutively at a single children's hospital over a 5-year period were collected and evaluated. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…This type of complication is in no way unique to children, with the adult literature reporting the risk of postembolization hemorrhage after AVM embolization to be 4%-12%. 8,13,21,23,31 Putative causes of postembolization hemorrhage in adults, such as a high volume of embolic agent administered, 23 are likely equally applicable to children. In our experience, several factors contributed to the low complication rate after the neurointerventions we report here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of complication is in no way unique to children, with the adult literature reporting the risk of postembolization hemorrhage after AVM embolization to be 4%-12%. 8,13,21,23,31 Putative causes of postembolization hemorrhage in adults, such as a high volume of embolic agent administered, 23 are likely equally applicable to children. In our experience, several factors contributed to the low complication rate after the neurointerventions we report here.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have described the risks of endovascular embolization in children with specific individual diagnoses, 1,6,10,31 but an overall evaluation of the safety profile of all neurointerventional procedures in children has not been performed. In the present study, we reviewed our experience with diagnostic cerebral angiography and neurointerventions in children to assess whether the aforementioned challenges translate into an elevated morbidity rate in pediatric patients.…”
mentioning
confidence: 99%
“…A recent study of 25 children undergoing 38 procedures for Onyx embolization of AVMs reported an overall obliteration rate of 12%, with a procedural complication rate of 26.3% and no permanent neurological morbidity. 35 Given the potential for long-term AVM recurrence in children, even if complete angiographically confirmed obliteration is serendipitously achieved, we would proceed to resection, wherever feasible, regardless of the postembolization angiographic appearance. Complete obliteration is not the primary goal of our embolization sessions.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Although AVMs are less common in kids [5], they are still considered the most frequent abnormality of intracranial circulation in childhood [16], and they are the most common cause of spontaneous intraparenchymal hemorrhage in children. Pediatric AVMs could also present with recurrent seizures or headaches [17,18,19,20,21]. The natural history of AVMs in children is not well studied or understood; in part, this might be due to the initial emergent therapy of these lesions.…”
Section: Incidence and Natural Historymentioning
confidence: 99%
“…The complication rates after endovascular embolization could be as high as 26% (table 3) [18]. None of the cases reported has a permanent neurological deficit or died, and all complications resolved over time [19,53].…”
Section: Treatmentmentioning
confidence: 99%